Development of Relative Value Units for Unit Cost analysis of Medical Services in Vietnam - Riewpaiboon, Dr. Arthorn (Asian Journal of Pharmaceutics (AJP), 2018)
Context: The unit costs of hospital services are essential for hospital and public health management. There are alternative methods on the costing with different results. The relative value unit (RVU) method, which is also known as the â€œweight procedure methodâ€, is a method universally used in many countries due to its applicability. Aims: This study is aimed to develop RVU of hospital medical services for unit cost calculation in Vietnam. Settings and Design: Development of the RVU is designed by objective data approach where the RVUs were estimated based on results of unit cost analysis employing micro-costing from two provincial hospitals. Materials and Methods: From 776 services of Ha Nam Hospitals and 2064 services of Thu Duc Hospital, a reference list of 1,464 medical services was developed. Results: The standard unit cost used for health economic evaluation in Vietnam can possibly be developed thanks to the RVUs from this study. Conclusions: Due to the constant improvement of the health serviceâ€™s framework, the RVUs should be developed and updated continuously. Moreover, the RVUs of health centers and the other types of hospital should be studied further to complete for health economic evaluation.